India : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper paints a picture of the Indian economy that has made great strides, but has more to do to accelerate growth and reduce poverty. The paper assesses empirically whether India has entered a new phase of higher trend growth. Two alternative methodologies are used to disentangle underlying structural growth trends from shorter-term cyclical fluctuations around this trend. The paper focuses on a number of the reforms required to ensure that needed high growth can be achieved on a sustained basis.